2007
DOI: 10.1097/mjt.0b013e3180a7206e
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Prophylactic Activity of QR-435 Against H3N2 Influenza Virus Infection

Abstract: QR-435 is effective for both prevention of H3N2 viral transmission and prophylaxis. These preclinical results warrant further evaluation of its prophylactic properties against avian influenza virus infection in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Masks impregnated with QR-435 (a flavonoid component) were highly effective in blocking the passage of live H3N2 virus [23]. In vivo prophylactic activity of QR-435 was demonstrated against H3N2 influenza virus infection [24].…”
Section: Resultsmentioning
confidence: 99%
“…Masks impregnated with QR-435 (a flavonoid component) were highly effective in blocking the passage of live H3N2 virus [23]. In vivo prophylactic activity of QR-435 was demonstrated against H3N2 influenza virus infection [24].…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the studies described above, a number of studies have been done to show the adequacy of ferrets as models for testing vaccine efficacy (reviewed by van der Laan et al, 2008; {Huber, 2008 #4356;Parks, 2007 #4357} and the effectiveness of antiviral drug therapy (Smee et al, 2008; Oxford et al, 2007; Malakhov et al, 2006). …”
Section: Seasonal Influenzamentioning
confidence: 99%
“…Most notably some of these preparations were not only effective in the ferret model (Oxford et al , 2007a ) but also have already demonstrated clinical effi cacy during the SARS epidemic in 2003 (Lau et al , 2005 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%